Awal Waktu Salat Magrib Berdasarkan Ketinggian Daerah di Kabupaten Jeneponto (Studi Perbandingan Dengan Jadwal Waktu Salat Sepanjang Masa) - Kartini, Selvira Febriani; Alimuddin; Muh. Akmal, Andi (Universitas Islam Negeri Alauddin Makassar, 2024)
The determination of prayer times is based on the phenomenon of the sun that is visible to the five senses. As for astronomy, sunset time begins when the sun sets. The setting of the sun here means that the entire